An Example of the Use of Traditional Woodworking Hand Tools in Product Design Studies at the Institute of Design Technologies of the Faculty of Materials Science and Applied Chemistry of Riga Technical University - Gūtmane, Ilze; Kukle, Silvija; Kalniņš, Jānis; Zotova, Inga; Ķīsis, Artūrs (History of Engineering Sciences and Institutions of Higher Education, 2022)
Initially, hand tools were created to facilitate the processing of materials in manufacturing utility items. Tool design, technology, and ergonomics evolved along with the growing human ability to process new materials. The tool range has expanded to meet more diverse needs of the woodworking industry, adapting the tools for both universal use and specific functions. Understanding of the functionalities of woodworking hand tools is essential for observing the sequence of material processing and practical processing operations, as well as in building awareness of the properties of the wood material. This is ensured by the interaction between the operator, the tool, and the workpiece. An important aspect in raising awareness is the relatively low processing speed and the processing of the material with human-controlled movements. Treatment of wood with craft methods and tools reveals the characteristic properties of the material, including specifics of wood grain direction, the difference in the density of earlywood and latewood, and the difference in the longitudinal and transverse grain direction. It also allows understanding the most typical wood defects. To make the process of learning a wood material meaningful in the study process, it is integrated with product manufacturing, making students create a wooden puzzle. This process implies running a sequential crafting process from a solid pine board to a finished and functional product – a puzzle. Students have to make it following a uniform design drawing showing the proportions of the pieces and joints. While making a wooden puzzle, students choose the most appropriate tools for each processing stage. In the process, it is necessary to check, measure, mark, and cut the workpiece. The result is a three-dimensional product that may be assembled and disassembled. The assembly and disassembly process allows appreciating the role of processing accuracy in the course of work and its impact on the end result.